THE RIGHT TO GOOD ADMINISTRATION (AS ESTABLISHED BY THE CHARTER OF FUNDAMENTAL RIGHTS OF THE EUROPEAN UNION) - Danėlienė, Ingrida; Saudargaitė, Ieva (Teisė, 2016)
The article investigates the principle of good administration, i. e. the right to good administration as established in Article 41 of the Charter of Fundamental Rights of the European Union. It looks into the possible influence, as well as the scope of the influence of the said provision, in determining the standard of protection of individual rights arising both from European Union and from national law in Lithuania. The article analyses the concept of the right to good administration on both the supranational and national levels; an emphasis is also laid on the contents of the principle of good administration in protecting individual rights, which had possibly been infringed by the acts or inaction of entities of public administration. The article provides the conclusions on the impact of the right to good administration (as established in Article 41 of the Charter of Fundamental Rights of the European Union) on the protection of individual rights within administrative jurisdiction.